ENCAPSULATION EFFICIENCY AND THERMAL STABILITY OF ORANGE ESSENTIAL OIL MICROENCAPSULATED BY SPRAY DRYING AND BY COACERVATION - Zawadzki, Sônia F.; Perussello, Camila A.; Müller, Priscila S.; Scheer, Agnes de P. (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2016)
Orange essential oil was microencapsulated by spray drying using maltodextrin and modified starch as carrier agents, and also by coacervation using sodium alginate. The influence of different microencapsulation methods and carriers on the microscopic and thermal characteristics of the product and on the encapsulation efficiency of the microparticles was investigated. According to a technique based on headspace extraction coupled to gas chromatography, the encapsulation efficiencies were above 99 % for both methods, and the oil was composed mainly of D-limonene (95.7 %) and mircene (1.66 %). Coacervation and spray drying produced microparticles of 908.63 μm and 1.02 μm, respectively, which increased the thermal stability of the oil. Nonetheless, the coacervated microparticles showed higher thermal stability and boiling point than the spray-dried ones.